A brave new creativity. Issue 1 (1st September 2013) - Welch, Donald; Loy, Jennifer
Anyone who has taught design in higher education for any length of time knows that the parameters of their work have changed. Design is no longer industry based, but seen as an approach, an attitude, with ways of thinking that can contribute to all programmes across the university system. Ensuring that this new cohort are engaged in authentic, complex problem-based learning and empowered in that learning is a challenge in itself but one of the most important teaching issues is how to instil genuinely creative thinking in students tackling 'messy' [i.e. 'wicked'] problems, unencumbered by the attitudes and approaches of the past. This article discusses the difficulties in achieving the creative learning aims involved, highlights areas that are yet to be resolved and suggests the use of a cognitive apprenticeship model combined with a practical, incremental teaching and assessment model of creativity as a contribution to the way forward.